2013
DOI: 10.1155/2013/174506
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Stigma in Men Who Have Sex with Men in Hanoi, Vietnam: Assessment of a Homosexuality-Related Stigma Scale

Abstract: Objective. To develop and assess a homosexuality-related stigma scale among men who have sex with men (MSM) in Hanoi, Vietnam. Methods. We conducted a cross-sectional study using respondent-driven sampling in Hanoi, Vietnam, in 2011. We used a cross-validation approach. Factor analysis was performed, and interitem correlation matrices were constructed to identify the latent factor structures, examine the goodness of fit, and assess convergent and discriminant validity of the determined scales. Internal consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Finally, our study showed that those who had experienced stigmatization were significantly more likely to practice TS. To measure stigmatization, we decided to use the Homosexuality-Related Stigma Scale, developed and validated in Vietnam [38]. This scale takes into account all three types of MSM stigmatization (experienced, perceived and internalized).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study showed that those who had experienced stigmatization were significantly more likely to practice TS. To measure stigmatization, we decided to use the Homosexuality-Related Stigma Scale, developed and validated in Vietnam [38]. This scale takes into account all three types of MSM stigmatization (experienced, perceived and internalized).…”
Section: Discussionmentioning
confidence: 99%
“…c) Homosexuality-related stigmatization during the previous 6 months : we constructed the following three scales for homosexuality-related stigmatization, each scale ranging from 0 to 10, based on items from a previous study (S2 Appendix) [38]: “experienced homosexual stigmatization” (based on 5 items, Cronbach’s alpha = 0.83); “perceived homosexual stigmatization” (based on 11 items, Cronbach’s alpha = 0.54); and “internalized homosexual stigmatization” (based on 8 items, Cronbach’s alpha = 0.73).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, our study - which is the first to explore the different types of stigmatization (especially internalized) in MSM in West Africa – showed that MSM-TS were significantly more likely to have experienced stigmatization. To measure stigmatization, we decided to use the Homosexuality-Related Stigma Scale, developed and validated in Vietnam [33]. This scale takes into account all three types of MSM stigmatization (experienced, perceived and internalized).…”
Section: Discussionmentioning
confidence: 99%
“…c) Stigmatization during the previous 6 months: the following three sub-scores, ranging from 0 to 10, were constructed, based on items from a previous study (S2 appendix) [33]: “experienced stigmatization during the previous 6 months” (based on 5 items, Cronbach’s alpha=0.83); “perceived stigmatization” (based on 11 items, Cronbach’s alpha=0.54); and “internalized stigmatization” (based on 8 items, Cronbach’s alpha=0.73).…”
Section: Methodsmentioning
confidence: 99%
“…c) Stigmatization during the previous 6 months: three sub-scores were constructed ranging from 0 to 10. They were based on items taken from previous study (S3 Appendix) [37]: 1) “experienced stigmatization” (based on 5 items, Cronbach’s alpha = 0.58); 2) “perceived stigmatization” (based on 11 items, Cronbach’s alpha = 0.70); and 3) “internalized stigmatization” (based on 8 items, Cronbach’s alpha = 0.80).…”
Section: Methodsmentioning
confidence: 99%